Exploring the NΛ-NΣ coupled system with high precision correlation techniques at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Physics letters, 2022)
The interaction of Λ and Σ hyperons (Y) with nucleons (N) is strongly influenced by the coupled-channel dynamics. Due to the small mass difference of the NΛ and NΣ systems, the sizable coupling strength of the NΣ↔NΛ processes constitutes a crucial element in the determination of the NΛ interaction. In this letter we present the most precise measurements on the interaction of pΛ pairs, from zero relative momentum up to the opening of the NΣ channel. The correlation function in the relative momentum space for pΛ⊕p‾Λ‾ pairs measured in high-multiplicity triggered pp collisions at s=13 TeV at the LHC is reported. The opening of the inelastic NΣ channels is visible in the extracted correlation function as a cusp-like structure occurring at relative momentum k⁎=289MeV/c. This represents the first direct experimental observation of the NΣ↔NΛ coupled channel in the pΛ system. The correlation function is compared with recent chiral effective field theory calculations, based on different strengths of the NΣ↔NΛ transition potential. A weaker coupling, as possibly supported by the present measurement, would require a more repulsive three-body NNΛ interaction for a proper description of the Λ in-medium properties, which has implications on the nuclear equation of state and for the presence of hyperons inside neutron stars.
Online verfügbar 4 July 2022, Artikelversion 15 July 2022
Gesehen am 03.03.2023
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V. Feuillard, P. Glässel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband, A. Yuncu [und viele weitere]